LiSurveying: A high-resolution TLS-LiDAR benchmark. (October 2022) - Lugo, Gabriel; Li, Ryan; Chauhan, Rutvik; Wang, Zihao; Tiwary, Palak; Pandey, Utkarsh; Patel, Archi; Rombough, Steve; Schatz, Rod; Cheng, Irene
Abstract: Outdoor point-cloud object localization is an essential processing step for urban scene analysis and modeling in numerous applications, especially in land surveying and site analysis. Given the increasingly use of Terrestrial Laser Scanning (TLS) and LiDAR 3D data acquisition, numerous annotated point-cloud datasets are available and can be used to evaluate computer vision and machine learning based algorithms. Nevertheless, current point-cloud datasets mainly focus on object detection and classification in autonomous driving or urban planning type of applications, and share redundant object classes, e.g., trees, vehicles and pedestrians, which limit their usefulness for land surveying and site analysis. This paper introduces a novel 3D benchmark dataset LiSurveying, which is a large-scale point-cloud dataset with over a billion points and uncommon urban object categories in complex outdoor environments. Our dataset incorporates more urban object classes than existing datasets. Its instances have diverse point densities, shapes and dimensions, which also impose a challenge for point-cloud detection and classification algorithms. We conducted baselines experiments for point-cloud classification using machine learning classifiers and deep learning methods on different subsets of the LiSurveying dataset, and we are able to demonstrate that the various types of object classes, number of instances per class, distribution of object points, and variety of complex scenes, make this LiSurveying benchmark dataset suitable for evaluating 3D point-cloud classification, semantic segmentation, and object detection algorithms. Graphical abstract: Highlights: Large-scale (point-wise and 3D bounding boxes) TLS-LiDAR dataset for Land Surveying. 3D Urban benchmark for object classification y detection. Learning-based methods applied on complex urban environments. Comparative performance of existing algorithms for LiDAR classification.